Gender effects on postural sway during rifle aiming - Zajac, R.; Basiaga, J.; Slomka, K.; Juras, G. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Eight male and eight female subjects without prior shooting experience took part in the experiment. The aim of this study was to determine gender effects on postural sway characteristics and rambling and trembling components during rifle aiming. Subjects were tested with the use of force platform in quiet standing, in shooting position, and in shooting position with additional visual feedback, three times in each condition. Rambling (RM) Trembling (TM) signal decomposition was used to process the data. Center of the pressure sway range (COPra), mean velocity (COPvel), COP root mean square (RMS), and the rambling and trembling displacement length (RMlen, TRlen) in the anterior-posterior (AP) and medial-lateral (ML) directions were analyzed variables. The results showed significant changes in behaviour due to increased levels of task difficulty effect of gender.